Attitudes of medical students to general practice: a multinational cross-sectional survey. (30th November 2020) - Avian, Alexander; Poggenburg, Stephanie; Schaffler-Schaden, Dagmar; Hoffmann, Kathryn; Sanftenberg, Linda; Loukanova, Svetla; Bachler, Herbert; Gehrke-Beck, Sabine; Petek Ster, Marija; Becker, Annette; Herrmann, Markus; Frese, Thomas; et al.
Abstract: Background: A shortage of general practitioners (GPs) is common to many European countries. To counteract this, it is essential to understand the factors that encourage or discourage medical students from choosing to become a GP Objective: To evaluate medical students' attitudes towards general practice and to identify factors that discourage them from considering a career as a GP. Methods: In this multinational cross-sectional online survey, 29 284 students from nine German, four Austrian and two Slovenian universities were invited to answer a questionnaire consisting of 146 closed and 13 open-ended items. Results: Of the 4486 students that responded (response rate: 15.3%), 3.6% wanted to become a GP, 48.1% were undecided and 34.6% did not want to be a GP. Significant predictors for interest in becoming a GP were higher age [odds ratio (OR) = 1.06; 95% confidence interval (CI) = 1.02–1.10], positive evaluation of the content of a GP's work (OR = 4.44; 95% CI = 3.26–6.06), organizational aspects (OR = 1.42; 95% CI = 1.13–1.78), practical experience of general practice (OR = 1.66; 95% CI = 1.08–2.56) and the country of the survey [Slovenian versus German students (Reference): OR = 2.19; 95% CI = 1.10–4.38; Austrian versus German students (Reference): OR = 0.50; 95% CI = 0.32–0.79]. Conclusion: Strategies to convince undecided students to opt for a career as a GP should include a positive representation of a GP's work and early and repeated experience of working in a general practice during medical school.